2009
DOI: 10.1515/cclm.2010.042
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osteopontin concentrations in preeclampsia – is there an association with endothelial injury?

Abstract: Background: It has been previously reported that plasma osteopontin (OPN) concentrations are increased in cardiovascular disorders. The goal of the present study was to determine plasma OPN concentrations in healthy pregnant women and preeclamptic patients, and to investigate their relationship to the clinical characteristics of the study subjects and to markers of inflammation wC-reactive protein (CRP)x, endothelial activation wvon Willebrand factor antigen (VWF:Ag)x or endothelial injury (fibronectin), oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Improved capillary penetrability secondary to endothelial destruction seems to be partly responsible for this result [13]. There were A significant increase in mean levels of Inhibin B and Osteopontin, in group A [pregnant women with preeclampsia] comparing to group B [healthy pregnant women] (P<0.01) as shown in Table (2). A significant increase in mean levels of Osteopontin in the present study agreement with Stenczer B et al [14] while another study showed no significant difference in plasma Osteopontin concentrations between the preeclamptic and the control group [15]. The extravillous trophoblasts of the human placenta also express Osteopontin, which regulates the invasiveness of these cells [16] Osteopontin may be released from the vessel wall into the peripheral circulation in cases of extensive endothelial injury, and may be used as a marker of endothelial injury in patient with preeclampsia.…”
Section: Resultssupporting
confidence: 93%
“…Improved capillary penetrability secondary to endothelial destruction seems to be partly responsible for this result [13]. There were A significant increase in mean levels of Inhibin B and Osteopontin, in group A [pregnant women with preeclampsia] comparing to group B [healthy pregnant women] (P<0.01) as shown in Table (2). A significant increase in mean levels of Osteopontin in the present study agreement with Stenczer B et al [14] while another study showed no significant difference in plasma Osteopontin concentrations between the preeclamptic and the control group [15]. The extravillous trophoblasts of the human placenta also express Osteopontin, which regulates the invasiveness of these cells [16] Osteopontin may be released from the vessel wall into the peripheral circulation in cases of extensive endothelial injury, and may be used as a marker of endothelial injury in patient with preeclampsia.…”
Section: Resultssupporting
confidence: 93%
“…Osteopontin (OPN) is involved in adhesion and signal transduction at the uterine-placental interface during implantation and placentation [73]. Importantly, OPN acts as a pro-inflammatory Th1 type cytokine in vivo [74] and preeclamptic patients with extensive endothelial injury are characterized by increased plasma levels of OPN [75]. Thus, the increased OPN production by PE-PDMSCs that we reported could cause and/or further contribute to the aberrant placental inflammation underlying preeclampsia.…”
Section: Discussionmentioning
confidence: 63%
“…Given that late pregnancy is an insulin-resistant state and that women with gestational diabetes are known to have even increased insulin resistance, osteopontin might be implicated in the development of insulin resistance during pregnancy per se and/or the aggravation of insulin resistance in gestational diabetes. Of note, osteopontin was reported to be elevated in women with preeclampsia [10] and like gestational diabetes, also preeclampsia has been linked to increased insulin resistance during pregnancy [11].…”
Section: Introductionmentioning
confidence: 99%